Rett syndrome - Kaufmann, Walter E.; Percy, Alan K. (Clinics in Developmental Medicine, 2017)
Among the vast body of literature that has grown around Rett syndrome, this volume is the first to be aimed at both clinicians and researchers.It presents a comprehensive overview of the disorder and examines the areas where gaps in knowledge are most significant.Rett Syndrome is intended to be a guide for both initial examination and in-depth study of the disorder. It is a practical text for the physician approaching the disorder for the first time and a valuable reference resource for the specialist or researcher.